Crystal Structures of Diaryliodonium Fluorides and Their Implications for Fluorination Mechanisms. Issue 18 (2nd March 2017) - Lee, Yong‐Sok; Chun, Joong‐Hyun; Hodošček, Milan; Pike, Victor W.
Abstract: The radiofluorination of diaryliodonium salts is of value for producing radiotracers for positron emission tomography. We report crystal structures for two diaryliodonium fluorides. Whereas diphenyliodonium fluoride (1 a ) exists as a tetramer bridged by four fluoride ions, 2‐methylphenyl(phenyl)iodonium fluoride (2 a ) forms a fluoride‐bridged dimer that is further halogen bonded to two other monomers. We discuss the topological relationships between the two and their implications for fluorination in solution. Both radiofluorination and NMR spectroscopy show that thermolysis of2 a gives 2‐fluorotoluene and fluorobenzene in a 2 to 1 ratio that is in good agreement with the ratio observed from the radiofluorination of 2‐methylphenyl(phenyl)iodonium chloride (2 b ). The constancy of the product ratio affirms that the fluorinations occur via the same two rapidly interconverting transition states whose energy difference dictates chemoselectivity. From quantum chemical studies with density functional theory we attribute the " ortho ‐effect" to the favorable electrostatic interaction between the incoming fluoride and the o ‐methyl in the transition state. By utilizing the crystal structures of1 a and2 a, the mechanisms of fluoroarene formation from diaryliodonium fluorides in their monomeric, homodimeric, heterodimeric, and tetrameric states were also investigated. We propose that oligomerization energy dictates whether the fluorination occurs through a monomeric or an oligomeric pathway. Abstract : Origin of the ortho effect : The " ortho effect" imparted by an o ‐alkyl group in the reaction of diaryliodonium salts with a fluoride ion is attributed to a favorable electrostatic interaction between the incoming fluoride and the o ‐methyl group in the transition state ( TS B ).